2012
DOI: 10.1021/jp305323s
|View full text |Cite
|
Sign up to set email alerts
|

Outstanding Catalyst Performance of PdAuNi Nanoparticles for the Anodic Reaction in an Alkaline Direct Ethanol (with Anion-Exchange Membrane) Fuel Cell

Abstract: The present article deals with the comprehensive electrocatalytic study of the binary and ternary combinations of Ni and Au with Pd for use as the anode component of a direct ethanol fuel cell (DEFC) operating with an anion-exchange membrane (AEM). The catalysts were grown on a carbon support by chemical reduction of the respective precursors. The information on surface morphology, structural characteristics, and bulk composition of the catalyst was obtained using transmission electron microscopy, X-ray diffra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
43
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 57 publications
5
43
1
Order By: Relevance
“…The results of the Tafel polarization study corroborate the findings of CV. Nearly the same values of Tafel plots were obtained on graphene supported NiPd binary catalysts [6], binary composite films of Pd and Ni on multiwalled carbon nanotubes (MWCNT) [36], carbon supported PdNi nanoparticles [35,37] and rather higher on PdNi nanoparticles supported on sulfonated MWCNT [38]. Figure 6 shows the CVs obtained at Pd 0.74 Ni 0.26 catalyst in 1 M NaOH +1.0 M C 2 H 5 OH solution at different scan rates.…”
Section: Electrochemical Characterization Of the Electrodeposited Samsupporting
confidence: 54%
“…The results of the Tafel polarization study corroborate the findings of CV. Nearly the same values of Tafel plots were obtained on graphene supported NiPd binary catalysts [6], binary composite films of Pd and Ni on multiwalled carbon nanotubes (MWCNT) [36], carbon supported PdNi nanoparticles [35,37] and rather higher on PdNi nanoparticles supported on sulfonated MWCNT [38]. Figure 6 shows the CVs obtained at Pd 0.74 Ni 0.26 catalyst in 1 M NaOH +1.0 M C 2 H 5 OH solution at different scan rates.…”
Section: Electrochemical Characterization Of the Electrodeposited Samsupporting
confidence: 54%
“…In particular, a great deal of interest has been focused on the use of Pd-based alloy catalysts as an alternative for EOR where the catalytic activity may be further increased by the addition of a second metal or metal oxide promoters through the effects mentioned above. Various Pd-based catalysts have been synthesized with the addition of one or more elements including Ni [110,111], Ag [112,113], Au [114][115][116], P [117], Co [118], Sn [80,110,119,120], Ru [53], Zn [121] as well as metal oxides like SnO2, CeOx, Co3O4, Mn3O4, NiO [102,[122][123][124][125] or on various substrates like graphene [126], carbon microspheres [127], nanowire [128], carbon fiber [118], etc.…”
Section: Pd Based Catalystsmentioning
confidence: 99%
“…Zhao's group [114] synthesized a monolayer or a sub-monolayer of Pd adatoms decorated on Au/C with different Pd:Au atomic ratios in the precursors via a chemical epitaxial growth method and found Pd1Au4 shows the highest specific activity due to the electronic effect between the Au support and the Pd decoration, and the enhanced poison resistance. To further tune the electronic and geometric effect of the catalysts, ternary catalysts PdNiAu [116] were synthesized which possessed a peak power density about three times that of the monometallic Pd catalyst, and twice that of the bimetallic PdNi catalyst. A relatively preferable C2 pathway on the Pd-Au-Ni catalyst compared to its single and binary counterparts in alkaline media was estimated by ion chromatography.…”
Section: Pd Based Catalystsmentioning
confidence: 99%
“…prepared bimetallic PdAu electrocatalysts via electron beam irradiation and showed that a Pd:Au ratios of 90:10 gives the highest power density (44 mW cm −2 at 85 °C) compared to pure Pd (25 mW cm −2 at 85 °C). Dutta et al 32. found that ternary catalyst Pd:Ni:Au possessed a peak power density about three times that of the monometallic Pd catalyst.…”
mentioning
confidence: 99%